Experiences of podiatrists in the delivery of routine foot care with self-management - Koh, Beatrice Hwee Jean; Hanquan, Arnold Hu; Leong, An-Qi Christel; Kok, Jian Min Jamie (Journal of the Foot & Ankle, 2024)
Objective: Explore the experiences of podiatrists in the provision of foot care and identify gaps in promoting self-care to their patients. Methods: This study adopted a qualitative research paradigm comprising semi-structured interviews with 16 podiatrists from diverse clinical settings and varying experiences from February to May 2023. The data was analyzed inductively to develop themes. Results: Four themes emerged from the data: 1) Provision of nail care service, 2) Perceived reasons for referral for podiatric nail care, 3) Self-management with various patient sub-groups, and 4) Effectiveness of self-management, all from our participants’ perspective. Podiatrists agree that pathological nails and high-risk feet warrant continual podiatry care. However, the majority are ambivalent about providing care for non-pathological nails due to fear, indifference, lack of social support, and physical limitations. Interviewees reported the importance of managing patients’ expectations of the role of podiatry in nail care from the first visit to avert potential over-reliance on the service. Clear explanations and equipping patients with the appropriate tools helped promote self-management. Conclusion: This paper examined the complexity of the demand for podiatry nail care services, focusing on podiatrists’ perspectives. It emphasized the importance of effective communication with patients to clarify the purpose of podiatry and to ensure sustainable podiatry care for the future. Level of evidence V; Therapeutic studies - investigating the results of treatment; Expert Opinion.